1997
DOI: 10.1002/(sici)1097-4628(19970919)65:12<2343::aid-app8>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Emulsion copolymerization of styrene andn-butyl acrylate in presence of acrylic and methacrylic acids: Effect of pH on kinetics and carboxyl group distribution

Abstract: The batch emulsion copolymerization of styrene with n-butyl acrylate in the presence of acrylic and methacrylic acids was investigated. Values of reaction rate and conversion observed at different pH values were examined. The effect of pH on the glass transition temperature of the polymers was also investigated and the results compared with model predictions. Its effect on the distribution of the carboxyl groups at different positions within the emulsion system (surface and core of particles, and in the aqueou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
53
0
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 13 publications
6
53
0
1
Order By: Relevance
“…Thus this feature can be explained by a diffuse transition between the core and the corona as a consequence of the incorporation of hydrophobic units during the copolymerization of carboxylic monomers. This is consistent with most of the emulsion polymerization studies that conclude to "buried" hydrophilic units that compose 1-5% of the total core volume [37,58,59].…”
Section: The Interface Between the Core And The Corona Of The Particlesupporting
confidence: 90%
“…Thus this feature can be explained by a diffuse transition between the core and the corona as a consequence of the incorporation of hydrophobic units during the copolymerization of carboxylic monomers. This is consistent with most of the emulsion polymerization studies that conclude to "buried" hydrophilic units that compose 1-5% of the total core volume [37,58,59].…”
Section: The Interface Between the Core And The Corona Of The Particlesupporting
confidence: 90%
“…With MAA, there is significantly less water-soluble polymer formed and the MAA copolymer in the particle is somewhat more evenly dispersed within the particle. These dramatic differences between acrylic and methacrylic acids were reported in the study by Dos Santos et al, 3 where they contrasted the results for the two comonomers during the production of poly(styreneco-n-butyl acrylate) latices. At a pH of 2.2, they reported that 88% of the MAA is located in the interior portions of the particles, with 10% in the outer regions of the particles and only 2% in the water phase.…”
mentioning
confidence: 66%
“…There have been many studies done to determine the location of the acid polymer in the latex particles and in the aqueous phase surrounding them. [1][2][3][4] Another area of study has been the partitioning of the acid monomers between the aqueous and particle phases during polymerization. Acrylic, itaconic, and fumaric acids are highly partitioned to the water phase even at pH levels below the pKas of these acids, while methacrylic acid (MAA) is more reasonably balanced between the phases.…”
mentioning
confidence: 99%
“…The promoted dissociation of methacrylic acid is observed with pH increase. 18,19 The enhanced dissociation of methacrylic acid resulted in reduction of reaction rate suggesting reduction of product particle size. 20 All of these observations consistently indicate that the polystyrene particle size can be adjusted by controlling the ionization of comonomer of acrylic acid, which can be promoted by addition of ammonium hydroxide.…”
Section: Resultsmentioning
confidence: 99%